Case Report: Successful management of refractory palmoplantar pustulosis with upadacitinib - Yang, Boyun; Yu, Hanxiao; Yao, Wo; Wang, Huiying (Frontiers in Immunology, 2025)
Palmoplantar Pustulosis (PPP) is a rare chronic skin disorder characterized by recurrent sterile pustules on palms and soles, leading to significant pain and functional impairment. Treatments include topical medications, phototherapy, systemic treatments, and biologics, but nonconclusive strategy exists. Here we report a case of a 66-year-old Chinese woman who developed refractory PPP after COVID-19 vaccination, characterized by painful, itchy pustules on her hands and feet. Initial treatments such as topical corticosteroids, calcipotriol, methotrexate, and cyclosporine were ineffective. Due to potential hypersensitivity reactions post-vaccination and elevated Immunoglobulin (Ig)E levels, anti-IgE therapy was administrated. Omalizumab treatment resulted some improvement, but noticeable symptoms persisted. Upon switching to upadacitinib, the patient experienced rapid and complete resolution of pustules and desquamation, with continued symptom control and no severe adverse reactions over a year. Throughout the treatment, clinical symptoms and the patient’s quality of life were assessed using the Palmoplantar Pustular Psoriasis Area and Severity Index (PPP ASI), the Palmoplantar Pustulosis Physician Global Assessment (PPP PGA), and the Dermatology Life Quality Index (DLQI). Serum IgE and food-specific (FS)-IgG4 levels were monitored. Additionally, reductions in cytokine levels (interleukin (IL)-4, IL-13, IL-25, IL-33, and tumor necrosis factor (TNF)-α) were observed after upadacitinib treatment. This case highlights the potential of upadacitinib, as an effective treatment for PPP, emphasizing the need for further research into targeted therapies addressing multiple signaling pathways involved in PPP’s pathogenesis.